Wiktor Dega – wybitny lekarz i pedagog (1896–1995) – wspomnienie w dwudziestą rocznicę śmierci - Apanel, Anna Maria; Kotarski, Piotr (Biuletyn Historii Wychowania, 2015)
Wiktor Dega – a remarkable medical doctor and educator (1896–1995) – reminiscences on the 20th anniversary of his death This elaboration concerns reminiscences on a remarkable human being, medical doctor – an orthopaedist and educator – Wiktor Dega. It consists of two fundamental parts: a biographical part and the other showing the professor’s role in treating and developing a medical care for a child with motor dysfunction. It also presents Wiktor Dega’s academic and didactic activity and his efforts in arranging the first free of charge courses in orthopaedic gymnastics in Poznań primary schools for children with poor posture. This activity was deeply rooted in the professor’s interest in rehabilitation. Wiktor Dega was a co-founder and the first president of the Polish Association for Combating Disability [Towarzystwo do Walki z Kalectwem]. He was a member of the Executive Board of the Polish Academy of Sciences, a member of the Scientific Council at the Ministry of Health and Social Care, an expert for rehabilitation at the WHO and one of advisers of the World Health Fund in New York. For many years he was also a national rehabilitation specialist, the president of the Polish Orthopaedic and Traumatology Association as well as chief editor of the magazine called “Chirurgia Narządów Ruchu i Ortopedii Polskiej”. He was also an honorary citizen of Poznań.